CENTRAL AUDITORY DYSFUNCTION AS A HARBINGER OF ALZHEIMER’S DEMENTIA - Gates, George A. (2011)
OBJECTIVE: Confirm that central auditory dysfunction may be a precursor to the onset of Alzheimer’s Disease (AD) DESIGN: Cohort study SETTING: Research study center PARTICIPANTS: 274 volunteers from a dementia surveillance cohort were followed for up to 4 years after having complete audiometric assessment. 21 of the participants received a consensus diagnosis of AD after hearing testing. INTERVENTION: Three central auditory tests were performed: the Dichotic Sentence Identification, the Dichotic Digits, and the Synthetic Sentence Identification with Ipsilateral Competing Message. MAIN OUTCOME MEASURES: A new diagnosis of Alzheimer’s disease using the National Institute of Neurological and Communicative Diseases and Stroke–Alzheimer’s Disease and Related Disorders Association criteria at a consensus conference RESULTS: The mean scores on each CAD test were significantly poorer in the incident dementia group. Cox proportional hazards models with age as the time-scale were used to estimate the hazard ratio for incident dementia based on CAD test results. After adjusting for educational level, the hazard ratio for incident dementia in people with severe CAD based on a Dichotic Sentence Identification in free report mode of <50% was 9.9 (95% C.I. 3.6, 26.7). CONCLUSIONS: In these cases, CAD was a precursor to Alzheimer’s dementia. We recommend evaluating older adults complaining of hearing difficulty with CAD tests. Those with severe CAD should receive a modified rehabilitation program and be considered for referral for neurologic evaluation.